A framework for visual literacy competences in engineering education. Issue 2 (3rd April 2022) - Martín Erro, Alfonso; Nuere Menéndez-Pidal, Silvia; Díaz-Obregón Cruzado, Raúl; Acitores Suz, Adela
Abstract: Visual literacy is essential for engineers. Technological professions have important visual characterization, both in the transmission of information and problem-solving. This means that future engineers must be proficient at communicating, thinking, and learning visually. However, engineering curricula takes partially the need to have visually literate students. The VLEE project was established to develop learning resources to enhance engineers' visual skills and abilities. VLEE recently published the 'Visual literacy for Engineering Education Competence Framework', which, for the first time, addresses visual literacy learning specific to engineering. Our approach offers new opportunities for engineering students, following competency-based education, and attempts to contribute to a campus-wide collaborative effort to develop students' communication, learning, and critical thinking skills using visual materials. This guide is considered relevant for all educators and experts in engineering education in order to help them successfully tackle the challenges that future professionals will inevitably face in the 21st century.